The Effect of Waste Management Technology, Recycling Policy, and Community Participation on Waste Generation Reduction in East Java - Auliani, Restu; Andaningsih, IGP Ratih; Karyasa, Tungga Bhimadi (Westscience Press, 2024)
This research investigates the intricate interplay of Waste Management Technology, Recycling Policy, and Community Participation in East Java, aiming to discern their collective impact on Waste Generation Reduction. A diverse sample of 250 respondents was analyzed demographically, and their responses were subjected to a rigorous quantitative analysis, employing Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results affirm the validity of the measurement model, establish discriminant validity, and reveal robust structural relationships. Management Technology, Recycling Policy, and Community Participation demonstrate positive and significant associations with Waste Generation Reduction, underscoring the need for a multifaceted approach to sustainable waste management. The study enhances our understanding of waste dynamics in East Java and provides actionable insights for policymakers and practitioners to formulate targeted interventions.